Seeing ghosts: crisis, ruin, and the creative industries. Issue 5 (3rd September 2019) - Brodie, Patrick
ABSTRACT: The article analyzes the process of economic recovery and spatial regeneration following the 2007–2008 financial crisis in the Republic of Ireland. Focusing in particular on the place of the creative and media industries within these top-down logics of planning, zoning, and property development, the article points to the strategic mobilization of 'culture' since the crisis for various forms of continuous financial and spatial exploitation. Using the popular visualization of the 'ghost estate' phenomenon as a starting point, differing logics and affects of ruin emerge within the fore- and en-closed futures of crisis within the built environment. Governing bodies like NAMA continue to manage the 'recovery' in a state of continuous exception, ensuring that the processes of foreign direct investment and urban regeneration continue unchecked as the country careens deeper into a housing shortage. The article proposes using the same materials put forth by the corporations and planning bodies of the 'creative city' to analyze a point of violence and contention where public goods and culture become mobilized strictly for private profit.